Susceptible time window and endurable duration of cotton fiber development to high temperature stress - XU, Bo; ZHOU, Zhi-guo; GUO, Lin-tao; XU, Wen-zheng; ZHAO, Wen-qin; CHEN, Bing-lin; MENG, Ya-li; WANG, You-hua (Journal of Integrative Agriculture, 2017)
The development of the cotton fiber is very sensitive to temperature variation, and high temperature stress often causes reduced fiber yield and fiber quality. Short-term high temperature stress often occurs during cotton production, but little is known about the specific timing and duration of stress that affects fiber development. To make this clear, pot experiments were carried in 2014 and 2015 in a climate chamber using cotton cultivars HY370WR（less sensitive variety） and Sumian 15（heat sensitive variety）, which present different temperature sensitivities. Changes of the most important fiber quality indices（i.e., fiber length, fiber strength and marcironaire） and three very important fiber development components（i.e., cellulose, sucrose and callose） were analyzed to define the time window and critical duration to the high temperature stress at 34°C（max38°C/min30°C）. When developing bolls were subjected to 5 days of high temperature stress at different days post-anthesis（DPA）, the changes（Δ%） of fiber length, strength and micronire, as a function of imposed time followed square polynomial eq. as y=a＋bx＋cx~2, and the time around 15 DPA was the most sensitive period for fiber quality development in response to heat stress. When 15 DPA bolls were heat-stressed for different durations（2, 3, 4, 5, 6, 7 days）, the changes（Δ%） of fiber length, strength and micronire, as a function of stress duration followed logistic equations y=A_1-A_2/1＋（x/x_0）~p＋A_2. Referred to that 5, 10 and 15% are usually used as criteria to decide whether techniques are effective or changes are significant in crop culture practice and reguard to the fiber quality indices change range, we suggested that 5% changes of the major fiber quality indices（fiber length, fiber strength and micronaire） and 10% changes of fiber development components（cellulose, sucrose and callose） could be taken as criteria to judge whether fiber development and fiber quality have been significantly affected by high temperature stress. The key time window for cotton fiber development in response to the high temperature stress was 13–19 DPA, and the critical duration was about 5 days.